Female Leadership Portrayed Through Lady Jessica In Frank Herbert' S Dune 2 Movie Script - Naba, Julian; H, Hariyono (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This thesis explores the representation of female leadership through the character of Lady Jessica in Frank Herbert's Dune 2.Grounded in feminist literary criticism and Catalyst’s theoryof female leadership.the study examines how Lady Jessica . The findings  of thesis are 1) Lady Jessica do qualities of female leadership decisiveness, collaboration, authority, inclusivity, and strategic thinking.2) The  effects of Lady Jessica’s female leadership are on her son and their society. Lady Jessica's leadership has a huge positive effect, both on Paul as a future leader and on the Fremen as a society evolving towards political and spiritual awakening.